Activist theatre and the agitprop legacy* - Warstat, Matthias (Peripeti, 2023)
Political theatre today seems to be dominated once again by activist approaches that want to have a direct impact on political conflicts with a clear agenda. When it comes to interpreting this new liaison of theatre and activism, it seems nearly unavoidable to look back at the historical avant-gardes around 1930. With the contemporary situation as a starting point, this article analyses the agitprop tradition focusing on the German example. It discusses to what extent one can speak of an agitprop legacy in Germany despite the dissolution of the agitprop groups under the Nazi regime; when and in what this legacy becomes recognisable and how today’s activist theatre groups refer to the models, problems and crises of the historical agitprop troupes.